A Brief Overview of Medical Software Tools Used in MR Image Segmentation - Memis, Abbas; Albayrak, Songul; Bilgili, Fuat (IEEE, 2018)
In this paper, various medical software tools, which have been developed for the manual, semi-automatic or fully-automatic segmentation of magnetic resonance (MR) images, and some features of these software tools are presented and discussed. MR imaging is one of the medical imaging modalities which are frequently preferred by the clinicians and surgeons. Segmentation of the MR images in clinical researches and in clinical engineering-based studies is emerging as a considerable requirement for the analysis of the disease images and the diseases. Medical software tools have been developed to meet this need and to provide facilities for the clinicians, surgeons and researchers in computer-aided research projects they conduct. Currently available MR image segmentation tools have many differences when considering criteria such as design, graphical-user interface and functions they provide. In this short review study, we briefly summarized 10 different MR image segmentation software tools highlighted in clinical researches and engineering studies and these software tools have been introduced.
Keywords: medical software tools; MR image segmentation; MR segmentation tools; Engineering; Medical Informatics; Medical Laboratory Technology